(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The field of oculomotor abnormalities (OMA) is of clinical and social importance. There is a group of OMA of unknown etiology. Purpose: To investigate the presence of DNA of herpesviruses venous blood of patients with OMA resulting from lesions of cranial nerves (CN) III and/or VI. Materials and Methods: Thirty-five patients with OMA of unknown etiology underwent examination. Whole venous blood samples were collected for detection of herpes simplex virus type 1/2 (HSV1/2), cytomegalovirus (CMV), Epstein Barr virus (EBV), human herpes virus 6 (HHV6), HHV7, varicella-zoster virus (VZV), and HHV8 DNA using polymerase chain reaction. Results: HHV7 was most common (16 patients; 45.7%), followed by EBV (5; 14.3%), HHV6 (2; 5.7%), HSV1/2 (1 patient) and CMV (1 patient). Eight patients (22.8%) were found to have two viruses. Of these, 6 had both EBV and HHV7, one had both EBV and HHV6, and one had both HHV6 and HHV7. In addition, 2 patients (5.7%) were found to have three viruses, EBV, HHV6, and HHV7. Conclusion: For patients with OMA of unknown etiology, the venous blood should be tested by PCR for herpesviruses.